Sistem Informasi Persediaan Barang Habis Pakai Pada Dinas Lingkungan Hidup - Kurniawansyah, Deni; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2023)
The rapidly expanding of information technology nowadays as well as the implementation of computerized systems has almost been used in all fields, including at Environment ServiceJambi City. These days, Environment Services in Jambi city still using manual methods in the way of consumable items management. The aim of this study is to analyze, design, consumables inventory information system, receipt of consumables, demand for consumables, distribution of consumables, and recording reports used UML Unified Modeling Language) that are consist of Use Case Diagram, Activity Diagram Dan Class Diagram and design to the extent of prototype. This research produces a prototype information system of consumable items supplies that can be manage by computerized system that can present reports of consumables needed daily or every month thatcan be applied to support the entire inventory information system of consumablesitem in at Environment services in Jambi city.